Prevalence and Antibiotic Resistance of Staphylococcus Species on Toilet Seats in Federal University Wukari, Taraba State, North-Easthern Nigeria - Briska, Joyce; Hammuel, Chrinius (Darul Yasin Al Sys, 2024)
Staphylococcus species are commensal bacteria and a major human pathogen that causes a wide variety of clinical manifestations. The most challenging feature of the Staphylococcus species bacterium is its rapid dissemination to humans and through toilet seats. The aim of this research is to assess for the presence of Staphylococcus species. A total of 20 toilet seat swab samples were obtained. The isolates were identified using biochemical techniques and were confirmed using microgen identification kits. A total of 16 (80%) isolates were identified as Staphylococcus species and 14 (87.5%) were identified as Staphylococcus aureus and 2(12.5%) as Staphylococcus epidermis. The antibiotic susceptibility test was carried out using Kirby Bauer antibiotic disk method. The prevalence of Staphylococcus species was 87.5% and 12.5% of Staphylococcus aureus and Staphylococcus epidermidis respectively. Most of the isolates were resistant to Ceftazidime, Erythromycin, Gentamicin, Levofloxacin, and Azithromycin due to the over use of the drug making most organism develop mechanism of resistance and acquiring resistance against them. Rifampin was more effective to Staphylococcus aureus in this research. The multiple antibiotic indices indicates that 87.5% of 87.5%, 12.5% of Staphylococcus aureus and Staphylococcus epidermidis and 12.5% Staphylococcus epidermidis had multiple antibiotic index greater 0.20. The presence of multi -drug resistant Staphylococcus species in this research emphasizes the need to formulate hygiene measures to prevent possible dissemination of Staphylococcus species and other transmissible pathogens to students and staff in the university.